2012
DOI: 10.1097/mat.0b013e31826feeca
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Ventricular Assist Device System

Abstract: Inadequate research exists regarding testing of a ventricular assist device (VAD) for susceptibility to radiation damage. Specifically, minimal data are available to radiation oncologists prescribing treatment plans for patients with an implanted VAD. As the number of implanted devices increases, patients requiring radiation at tissue sites near or at the device will increase. The purpose of this study is to provide the first analysis of radiation effects of proton beams on VADs. Five left VAD (LVAD) pumps (He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The secondary findings of this study regard image quality and retention of radiotracers inside the pump. Our previous testing of x-ray and proton radiation therapies on the HVAD pump (a pump that is currently commercially available from HeartWare Ò , Inc.) showed scattering and attenuation on the images (16,17). PET imaging in the current study clearly showed the inflow and outflow regions of the pump; only the portion of the pump with the spinning impeller was obscured (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…The secondary findings of this study regard image quality and retention of radiotracers inside the pump. Our previous testing of x-ray and proton radiation therapies on the HVAD pump (a pump that is currently commercially available from HeartWare Ò , Inc.) showed scattering and attenuation on the images (16,17). PET imaging in the current study clearly showed the inflow and outflow regions of the pump; only the portion of the pump with the spinning impeller was obscured (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…The impeller contains multiple large rare earth motor magnets, which are driven by electromagnetic force. This device further has an external microprocessor‐based controller, connected to the internal pump via a percutaneous driveline, which operates the pump, manages power sources, monitors pump function, provides diagnostic information, and stores pump parameter data …”
Section: Discussionmentioning
confidence: 99%
“…They further suggested that computer modeling underestimates the pretreatment dose in patients when the device is in the radiation field . Similarly, no change in HVAD function (n = 5) was found in response to proton beam therapy up to 70 GyE . No case reports of photon radiation in the specific setting of a third‐generation LVAD exist, although 4 case reports of safe treatment with radiation in earlier generation LVADs are available …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations